Visual Ranking of Link Structures - Brandes, Ulrik; Cornelsen, Sabine (Journal of Graph Algorithms and Applications, 2003)
Methods for ranking World Wide Web resources according to their positionin the link structure of the Web are receiving considerable attention,because they provide the first effective means for search engines tocope with the explosive growth and diversification of the Web. Closelyrelated methods have been used in other disciplines for quite some time. <!----> We propose a visualization method that supports the simultaneousexploration of a link structure and a ranking of its nodes byshowing the result of the ranking algorithm in one dimension andusing graph drawing techniques in the remaining one or twodimensions to show the underlying structure. We suggest to use asimple spectral layout algorithm, because it does not add to thecomplexity of an implementation already used for ranking, butnevertheless produces meaningful layouts. The effectiveness of ourvisualizations is demonstrated with example applications, in whichthey provide valuable insight into the link structure and theranking mechanism alike. We consider them useful for the analysisof query results, maintenance of search engines, and evaluation ofWeb graph models. <!---->